PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT)BERMEDIAKAN QUESTIONS BOX TERHADAP HASIL BELAJAR IPA - Azira, Azira (Journal for Lesson and Learning Studies, 2018)
This study was conducted based on several problems as follows. 1) Students' science learning achievements were still low. 2) Students still loved to play in lessons and they didn’t pay attention to the learning process. 3) The teacher tended to use the classical learning method in the school. 4) Teachers rarely use instructional media. This study aims to determine the effect of Teams Games Tournament model with the assistance of questions box towards the learning achievement of 5th grade students in MIN 2 Buleleng Buleleng sub-district in the academic year 2017/2018 in Natural Sciences subject. The population of this study is 5th garde in MIN 2 Singaraja Buleleng Sub-District in academic year 2017/2018 in which the total number of students are 93. The sample of this research is the 5th grade B class at MIN 2 Buleleng which amounted to 32 students and 5th grade A class in MIN 2 Buleleng which amounted to 30 students. Data were collected by multiple choice test with 30 items of questionnaire. The data collected were analyzed using descriptive and inferential statistical analysis (t-test). Based on the results of analysis, obtained thit> ttab. This means that there is effect learning model of Team Games Tournament (TGT) in form of questions box on the 5th grade students science learning achievement in MIN 2 Buleleng Buleleng sub-district in the academic year 2017/2018. Keywords : learning achievement, natural science subject, TGT